EVALUATION OF THE RADIATION SITUATION IN THE OBSERVATION AREA OF THE VOLGODONSK NUCLEAR POWER PLANT DURING 2007-2009 - S. I. Prokopenko; A. N. Barkovsky; V. Yu. Golikov; M. V. Kalinina; M. Yu. Soloviev (Радиационная гигиена, 2016)
This article presents the results of radiation monitoring which was performed in the observation area of the Volgodonsk NPP (VNPP) during 2007-2009. Calculations done using the obtained results for artificial exposure of population living in the observation area of the VNPP are presented. It is shown that annual exposure doses of population living in the observation area of the VNPP do not exceed 10 мSv per year.